Left atrial appendage strain and strain rate using cardiovascular magnetic resonance feature tracking: preliminary study on feasibility and reproducibility. Issue 6 (June 2022) - Cau, R.; Bassareo, P.; Cademartiri, F.; Saba, L.
Highlights: LAA function is an important marker to predict adverse cardiovascular events. LAA strain could be an additional tool to assess LAA phasic function. 2D-CMR-FT allows to quickly assess LAA strain and SR parameters.